2017
DOI: 10.21873/anticanres.11376
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Renal Cell Carcinoma of Native Kidneys in Renal Transplant Recipients: A Single-center Experience

Abstract: Most RCCs in renal transplant recipients are low-stage, low-grade tumors with a favorable prognosis. Their diagnosis is usually incidental. RCC development in the native kidney of renal transplant recipients is an early event, frequently observed within 4 to 5 years after transplantation. The different natural history of these tumors is still undefined. Further research is needed to determine whether these differences are due to particular molecular pathways or to biases in relation to the mode of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…While the exact etiology of the increased risk of RCC in KTx remains unclear, it is likely linked to the immunosuppressed state [4]. Reported risk factors for post-KTx RCC include older age, male sex, African descent, excess body weight, smoking, hypertension, history of acquired cystic kidney disease (ACKD), previous RCC prior to KTx, and longer pre-transplant dialysis duration [3,6,18,23,29,31,34,35,65,66,67]. Studies have shown that causes of ESRD before KTx may also affect the incidence of post-KTx RCC [14,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…While the exact etiology of the increased risk of RCC in KTx remains unclear, it is likely linked to the immunosuppressed state [4]. Reported risk factors for post-KTx RCC include older age, male sex, African descent, excess body weight, smoking, hypertension, history of acquired cystic kidney disease (ACKD), previous RCC prior to KTx, and longer pre-transplant dialysis duration [3,6,18,23,29,31,34,35,65,66,67]. Studies have shown that causes of ESRD before KTx may also affect the incidence of post-KTx RCC [14,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…RCC in patients who have undergone kidney transplantation occurs more often in the native kidney than in the renal allograft, although the reasons for this are not fully understood; risk factors that have been suggested including the type of immunosuppressant and the duration of immunosuppressive treatment, chronic native kidney disease, recipient’s age, and pre-transplantation dialysis duration [16]. While the etiology of increased risk of RCC remains elusive, and data are lacking on epidemiology and management of this solid renal mass in both native and allograft kidneys [12], the chronic immunosuppressed state of transplantation patients has been suggested to be an associated factor [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of RCC in native kidneys among renal allograft recipients is 15-100 times higher than in the general population [ 3 ], de novo RCC in renal allograft is a very rare event. In 1995, Penn et al [ 7 ] from the CTTR (Cincinnati Transplant Tumor Registry) reported 24 cases among 7596 cancers in kidney allograft recipients from 1968 until 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Four tumors were clear cell RCC and one was a papillary RCC. Patients from all these studies had an excellent survival after simple surgical treatment, whether after nephron sparing surgery or graft nephrectomy [ 3 – 6 ]. CDC of Bellini as observed in our patient is an uncommon variant of RCC, which represents less than 1% of all RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation